Yarn selection for weaving process to determine the parameters in OE rotor spinning machine by using TOPSIS methodology - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2015)
Selection of the optimum OE rotor spinning machine parameters for yarn production which is used in weaving process is a multi-criteria decision-making problem. For the selection of the optimal spinning machine parameters, alternative yarns produced in OE rotor spinning machine with each different parameters combined are needed. The aim of this paper is to propose TOPSIS to select the optimum OE rotor spinning machine parameters for yarn production which is used in weaving process. Therefore, in this study there are three machine parameters which are rotor surface, beater-wire profile and navel type. For each parameter different types are chosen like bronze and diamond rotor surface, OB 20 and B174 beater-wire profiles and finally CK, CK4 and CK8 navel types. By using each of the parameters Ne 30 rotor spun yarn is manufactured for the use in a weaving machine. Ultimately, 12 different yarn alternatives will be obtained for the yarn selection. Possible alternatives are ranked on the basis of the yarn quality parameters by the TOPSIS methodology and the best alternative for increasing weaving machine efficiency is selected. According to the final ranking, the spinning condition in which the sample is spun by using a diamond rotor surface, an OB 20 beater-wire profile and a CK navel type has the highest closeness coefficient to the ideal solution with the 0.981 score.
Keywords: weaving; OE rotor-spun yarn; TOPSIS methodology; imperfection; tenacity; MULTICRITERIA DECISION-MAKING; NAVEL SELECTION; AHP